Autómatas programables - Valencia Figueroa, Javier; Rodríguez Leitao, Jorge Mario; Rosales Luna, René; Tapias Albino, Sergio (My University, 1995)
High accuracy metering is a key requirement in a variety of industries, but is especially important for Bach, Blending, Material Movement, and Energy Management applications. In addition, Pulse/frecuency transducers are broadly applied in a variety of control applications.
Keywords: automatización; P.L.C.; estructura; siemens; programación; aplicaciones